Effect of Rotor Current Control for Wound Rotor Induction Generator on the Wind Turbine Performance - Mahmoud Rabie Barakat (Institute of Advanced Engineering and Science, 2012)
This paper presents the effect of rotor current control of wound rotor induction generator driven by wind turbine during different operation modes when varying the rotor resistance. The studied modes are wind speed variation, starting especially at high wind speed. Moreover, the effect of the proposed control on short circuit and critical fault clearing time is investigated.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.213